Effect of waste crab shell powder on matrix asphalt - Han Biao; Xing Yongming; Li Chao; Yan Jingchen; Zhang Xing; Zhang Lingyu (Reviews on Advanced Materials Science)
In order to solve the problems of depleting petroleum asphalt resources and deteriorating pollution of marine products, a systematic study was carried out on the application prospect of waste crab shell (WS) powder as asphalt modifier. In this study, the physical properties of WS powder modified asphalt (WSA) were tested by blending different contents of WS powder into matrix asphalt; the high and low temperature rheological properties of WS powder modified asphalt were characterized by using Dynamic shear rheometer, Bending beam rheometer, and Multiple stress creep recovery test. In addition, the microscopic chemical properties and modification mechanism were analyzed by Differential scanning calorimetry, Fourier transform infrared spectroscopy, Atomic force microscopy, and Scanning electron microscope. It was shown that the WS powder enhanced the viscoelastic properties, temperature sensitivity properties, and permanent deformation resistance of asphalt. In addition, there was no obvious chemical reaction between the WS powder and the matrix asphalt, and no new chemical substances were generated; at the microscopic level, the WS powder and the matrix asphalt had good compatibility. In conclusion, the use of WS powder as a bio-based asphalt modifier to improve the resources and environmental issues have certain prospects.